(untitled) - Sahinoglu, Mehmet (Hoboken, N.J., 2007)
The book itself is a commendable achievement, and it deals with the security and software reliability theory in an integrated fashion with emphasis on practical applications to software engineering and information technology. It is an excellent and unique book and definitely a seminal contribution and first of its kind
Keywords: Computer security,Computer software,Computer systems,Bảo mật máy tính,Hệ thống máy tính; Reliability,Reliability,Độ tin cậy